Very stable mismatch duplexes: structural and thermodynamic studies on tandem G.A mismatches in DNA. - Ebel, S; Lane, A; Brown, T (1992)
We have used ultraviolet melting techniques to compare the stability of several DNA duplexes containing tandem G.A mismatches to similar duplexes containing tandem A.G, I.A, and T.A base pairs. We have found that tandem G.A mismatches in 5'-Y-G-A-R-3' duplexes are more stable than their I.A counterparts and that they are sometimes more stable than tandem 5'-Y-T-A-R-3' sequences. This is not the case for tandem G.A mismatches in other base stacking environments, and it suggests that tandem G.A mismatches in 5'-Y-G-A-R-3' sequences have a unique configuration. In contrast to tandem 5'-G-A-3' mismatches, tandem 5'-A-G-3' mismatches were found to be unstable in all cases examined.